The cosmopolitan tradition a noble but flawed ideal - Nussbaum, Martha C. (Martha Craven), 1947- (The Belknap Press of Harvard University Press, 2019)
The cosmopolitan tradition begins with Diogenes, who claimed as his identity "citizen of the world." Martha Nussbaum traces the cosmopolitan ideal from ancient times to the present, weighing its limitations as well as merits. Using the capabilities approach, Nussbaum seeks to integrate the "noble but flawed" vision of world citizenship with cosmopolitanism's concern with moral and political justice for all.--